2008
DOI: 10.1017/s1041610208007229
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge and attitudes of doctors toward the sexuality of older people in Turkey

Abstract: This study identified a low level of awareness of later life sexuality among Turkish medical doctors. These findings identify a need to improve the education and training of doctors at both undergraduate and postgraduate levels to enable them to provide better sexual health care to older people.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
32
2
7

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(42 citation statements)
references
References 17 publications
1
32
2
7
Order By: Relevance
“…A barrier that is often cited in the literature is providers' lack of training in older adult sexual health (Dogan, Demir, Eker, & Karim, 2008;Gott, Galena, Hinchliff, & Elford, 2004). Inclusion of sexual health content in medical schools has varied over the years and is reported as sexual health content generally, not population-specific content.…”
mentioning
confidence: 99%
“…A barrier that is often cited in the literature is providers' lack of training in older adult sexual health (Dogan, Demir, Eker, & Karim, 2008;Gott, Galena, Hinchliff, & Elford, 2004). Inclusion of sexual health content in medical schools has varied over the years and is reported as sexual health content generally, not population-specific content.…”
mentioning
confidence: 99%
“…However, another American study with gynecologists (21) had an average score of 81 on the American ASKAS scale, in which the scores range from 26 to 182, representing 35.2% of the possible score, what showed that the population of the present study had a more favorable attitude towards the sexuality of the elderly than the gynecologists. In literature, studies assessing the knowledge and attitude of the patients were not found, only surveys with students and health professionals (21,22) . These results are the first to be obtained from the application of this instrument in this population.…”
Section: Discussionmentioning
confidence: 99%
“…However, the sexual needs of the elderly have been ignored or even ridiculed. Unfortunately, healthcare professionals also hold a rather conservative or negative attitude toward sexuality in old age [29,30]. Even when professionals have a positive attitude towards sexuality in the elderly, their knowledge in this area is fairly limited [30,31].…”
Section: Sexual Problems In Old Agementioning
confidence: 99%
“…Unfortunately, healthcare professionals also hold a rather conservative or negative attitude toward sexuality in old age [29,30]. Even when professionals have a positive attitude towards sexuality in the elderly, their knowledge in this area is fairly limited [30,31]. Hence, it is essential to develop a more comprehensive sex education program in order to increase healthcare professionals' knowledge of sexuality in old age, and to cultivate a positive attitude in them.…”
Section: Sexual Problems In Old Agementioning
confidence: 99%